IDENTIFICATION OF THE ISOLATED COMPOUNDS FROM Zingiber amaricans BL. RHIZOME - Sugeng Riyanto (Universitas Gadjah Mada, 2007)
Five extracts were obtained from extraction of rhizomes of Zingiber amaricans. Hexane, dichloromethane and methanol extracts were obtained by maceration, while dichloromethane and acetone extracts the resulted of soxhlet extraction. By column chromatography technique 2,6,9-humulantrien-9-one (zerumbone) was isolated as the major constituent of the hexane, dichloromethane and methanol extracts. The minor constituents were phytosterol mixtures isolated from hexane and dichloromethane extracts. The mixtures consisted cholesterol, campesterol, stigmasterol and b-sitosterol. The structure elucidations of zerumbone was confirmed by spectroscopic method, whereas the phytosterol mixtures was identified by gas chromatography-mass.